EFFECT OF SOLVENT THE SELECTIVE SEPARATION OF PHYTOSTEROLS USING ZEOLITE - A.Widjaja A.Widjaja; Chuang Y.H. Chuang (Reaktor, 2006)
The effect of organic solvent on zeolite adsorption of sterols mixiture containing almost the same percentage of campesterol and B-sitosterol was investigated. Although pentane was found to give the highest adsorption rate than other solvents, but it was not chosen as the sovent due to its low boilingpoint and high volatility. Although iso-actane has a high boiling point and adsorption rate like pentane, however, since it shows lower  selectivity than other solvents, it was not considered as a good solvent. Based on the the selectivity study which shows that using hexane as the solvent campesterol was adsorbed more than B-sitosterol, and also based on the moderate boiling point of hexane, hexane wasconsidered the best solvent for the separation of campesterol and B-sitosterol by zeolite adsorption. It was found that adding up to 0.3% ethanol could increase the adsorption rate. Methanol, having the highest polarity among other solvents investigated, gave the highest desorption rate of campesterol adsorbed  on the zeolite surface. However, solvent selectivity in the desorption was lower than that in  adsorption.